Frailty worsens long-term survival in patients with colorectal cancer: a systematic review and meta-analysis - Han, Jiangxue; Zhang, Qin; Lan, Jiarong; Yu, Fang; Liu, Jie (Frontiers in Oncology, 2024)
Background Colorectal cancer (CRC) is the 3rd most common cancer in men and 2nd most common malignancy in females across the globe leading to high mortality rates. Frailty is an age-related syndrome that has been associated with high morbidity and mortality. This systematic review aimed to examine if frailty can predict long-term (>1 year) outcomes of patients with CRC. Methods This PROSPERO registered review examined the databases of PubMed, Embase, and Web of Science till 4th September 2023 for cohort studies assessing the association between frailty and long-term outcomes of CRC. Results 15 studies with 45288 patients were included. 6573 patients (14.5%) were frail. Meta-analysis demonstrated that frailty was associated with statistically significant poor overall survival (OS) (HR: 2.11 95% CI: 1.44, 3.08 I2 = 94%) (14 studies), cancer-specific survival (CSS) (HR: 4.59 95% CI: 2.75, 7.67 I2 = 38%) (2 studies), and disease-free survival (DFS) (HR: 1.46 95% CI: 1.28, 1.66 I2 = 0%) (5 studies) after CRC. Subgroup analysis for OS based on study type, location, sample size, stage of cancer, percentage with frailty, treatment, adjustment for CRC stage and comorbidities, and follow-up did not change the results. These results were not altered in significance on sensitivity analysis. Conclusion Our results show that frail CRC patients have poor OS and DFS as compared to non-frail patients. Variations in frailty measurement tools and high inter-study heterogeneity are major limitations of the review. Systematic review registration https://www.crd.york.ac.uk/prospero/, PROSPERO, CRD42023450586